2019
DOI: 10.1111/ans.15343
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic severity of knee osteoarthritis and its relationship to outcome post total knee arthroplasty: a systematic review

Abstract: Background Up to 20% of patients are dissatisfied after total knee arthroplasty (TKA). There are many contributing factors. The relationship between preoperative osteoarthritis (OA) severity and outcome post TKA remains unclear. This review explores the relationship between preoperative OA severity with patient reported pain, function and satisfaction post TKA. Methods A pre‐registered systematic review was performed using the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 42 publications
(243 reference statements)
1
22
0
1
Order By: Relevance
“…African Americans were well represented in our sample, but other races and ethnicities were poorly represented, with only 9 additional subjects, and this lack of representation reduces generalizability for these populations. Finally, our study did not account for preoperative knee OA severity, a known predictor of poor outcome (50). It is possible that African Americans had milder knee OA than the non–African Americans, although we found no data to suggest that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…African Americans were well represented in our sample, but other races and ethnicities were poorly represented, with only 9 additional subjects, and this lack of representation reduces generalizability for these populations. Finally, our study did not account for preoperative knee OA severity, a known predictor of poor outcome (50). It is possible that African Americans had milder knee OA than the non–African Americans, although we found no data to suggest that this is the case.…”
Section: Discussionmentioning
confidence: 99%
“…Pain and dysfunction in knee joints are the main clinical manifestations of patients with KOA, and the purpose of treatment should be relieving pain and improving the knee joint function, so as to improve the quality of life of patients [20][21][22][23]. is study showed that the HSS scores of patients with KOA after surgery were significantly higher than the score before surgery (P < 0.05), and the postoperative pain scores increased with time, indicating that the patients' pain was alleviated gradually.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the knee joint is the joint most commonly involved in osteoarthritis [20] . TKA is a standard treatment for end-stage knee disease and works well [2–5,8,15] . The walking function is the most essential part of daily life activities.…”
Section: Discussionmentioning
confidence: 99%
“…The knee joint is a relatively complex joint of the human body. [2,3,5,[8][9][10]15,17,19] It needs to complete a wide range of joint movements under the condition of carrying human body gravity to meet the needs of human body movement. Therefore, the knee joint is the joint most commonly involved in osteoarthritis.…”
Section: Os (Meanmentioning
confidence: 99%